Development of Bacterial Cellulose Membrane from Sulfation SCOBY Kombucha for Polymer Electrolyte Membrane Fuel Cell (PEMFC) Applications - Sauli Safitri; Khairuddin Khairuddin; Ni Ketut Sumarni (Jurnal Kimia Sains dan Aplikasi, 2026)
Electrolyte membranes are critical components in determining the performance of PEMFC systems. The use of commercial membranes remains constrained by high production costs, thereby necessitating the development of biomaterial-based alternatives. Cellulose derived from SCOBY Kombucha presents a promising candidate for electrolyte membranes, yet its intrinsic proton conductivity is insufficient and requires chemical enhancement. This study aimed to optimize the sulfation process to improve the electrochemical properties of SCOBY-based cellulose membranes. Variations in reaction time and sulfuric acid concentration were investigated, followed by characterization of the modified membranes through proton conductivity, ion-exchange capacity, swelling degree, mechanical properties, thermal stability, FTIR, and SEM-EDX analyses. The optimum condition was achieved at 2 hours and 2 M, yielding a proton conductivity of 5.44×10−2 S/cm−1, an ion-exchange capacity of 3.58 meq/g, and a swelling degree of 111%, while exhibiting moderate mechanical strength and good thermal stability. FTIR and SEM-EDX confirmed successful incorporation of sulfonic acid groups. Overall, the modification produced a membrane with enhanced proton conductivity and ion-exchange capacity, although further mechanical reinforcement is required for practical PEMFC applications.